Relationship between Region Abscess Maxillofacial and Climate in South Sulawesi - Andi Tajrin; Muhammad Ruslin; Abul Fauzi; Muhammad I. Rasul; Leen D. K. Seleng (DiscoverSys Inc., 2019)
Objective: To determine the relationship between regiomaxilofacialabscesses with the monsoon and dry seasons.Material and Methods: Type of research used in this study isdescriptive observational. The research design used in this study is thecross sectional study.Results: The results of this study are not significant in the designationof the relationship between abscess maxillofacial and climate in SouthSulawesi, because it is caused by several factors including the numberof samples and the interval of data used, as well as environmentalfactors such as temperature and air pressure.Conclusion: This study regarding the relationship betweenmaxillofacial region abscess and climate in South Sulawesi showedthat as many as 31 abscess cases in Ibnu Sina Hospital, 9 abscess casesin Unhas Teaching Hospital, 3 cases of abscesses in East of IndonesiaUniversity Hospital occurred during monsoon season, while 27 cases ofIbnu Hospital abscess Sina, 2 abscess cases in Unhas Teaching Hospital,3 abscess cases in East of Indonesia University Hospital occurredduring dry season. This indicates that there is a relationship betweenthe development of abscesses when it’s monsoon season or whenbarometric pressure is low.